Presence and Dermal Exposure to Benzene and Acetaldehyde in Hand Sanitizers Available in Taiwan - Chieh-An Cheng; Shih-Wei Tsai (Toxics, 2025)
The widespread use of alcohol-based hand sanitizers (ABHS) during and after the COVID-19 pandemic has raised concerns about potential exposure to harmful volatile organic compounds (VOCs), such as benzene, acetaldehyde, and other impurities, which may pose health risks. This study investigated the concentrations of ethanol, isopropanol, and 12 impurities, including benzene, acetaldehyde, and methanol, in 85 commercially available ABHS products in Taiwan using gas chromatography-mass spectrometry (GC-MS). The results revealed that 12 samples contained alcohol concentrations below the recommended 60% (v/v) threshold. Benzene and acetaldehyde were identified as the primary impurities, with mean concentrations of 0.84 μg/g and 22.39 μg/g, respectively, exceeding the US FDA interim limits. For frequent ABHS users, the average dermal exposure doses (DEDs) to benzene ranged from 3.17 × 10−2 to 15.5 μg/kg-bw/day, with children aged 2–11 years showing the highest non-carcinogenic risk (Hazard Quotient > 1) and cancer risk (6.37 × 10−5 to 9.33 × 10−4). The findings emphasize the need for stringent quality control of ABHS products and caution in their selection and use. This study provides critical insights into the health risks associated with ABHS in Taiwan, underscoring the importance of regulatory oversight to ensure consumer safety.